2019
DOI: 10.17533/udea.redin.20190731
|View full text |Cite
|
Sign up to set email alerts
|

Effective sericin-fibroin separation from Bombyx mori silkworms fibers and low-cost salt removal from fibroin solution

Abstract: Silk from Bombyx mori has two main proteins: fibroin and sericin. Fibroin is a protein that exhibits good biocompatibility and high surface reactivity, desirable properties for many biomedical applications. Sericin is related with adverse immune response in some medical uses. Therefore, its removal (degumming) is desirable in almost all fields, including the textile industry and biological applications. In this study, three degumming methods (distilled water, liquid neutral detergent and sodium carbonate solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The early attempts to employ SS in biomedical engineering failed due to immunological response and cytotoxicity [ 85 ]. This phenomenon was later attributed to a lack of suitable extraction and purification techniques [ 86 ]. Until recently, SS was regarded as a byproduct of the textile industry, with tons of leftovers produced each year since the chemical oxygen demand and SS content of the silk degumming wastewaters may be as high as 60 g/L and 30 g/L, respectively [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…The early attempts to employ SS in biomedical engineering failed due to immunological response and cytotoxicity [ 85 ]. This phenomenon was later attributed to a lack of suitable extraction and purification techniques [ 86 ]. Until recently, SS was regarded as a byproduct of the textile industry, with tons of leftovers produced each year since the chemical oxygen demand and SS content of the silk degumming wastewaters may be as high as 60 g/L and 30 g/L, respectively [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that sodium carbonate dissolved in boiling water is the most commonly used method for degumming silk for biomedical applications. Silk fibers which have been degummed are generally dissolved in inorganic salts such as high concentrations of LiCl, LiBr solution, , NaSCN solution, ZnCl 2 solution, or in a ternary solvent mixture comprising CaCl 2 /ethanol/water. ,,, Salts such as these are also capable of breaking hydrogen bonds, ultimately disassembling the β-crystalline structure of degummed silk. Purification is carried out by dialysis against water and removing salts and impurities in order to obtain pure SF .…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibers which have been degummed are generally dissolved in inorganic salts such as high concentrations of LiCl, LiBr solution, , NaSCN solution, ZnCl 2 solution, or in a ternary solvent mixture comprising CaCl 2 /ethanol/water. ,,, Salts such as these are also capable of breaking hydrogen bonds, ultimately disassembling the β-crystalline structure of degummed silk. Purification is carried out by dialysis against water and removing salts and impurities in order to obtain pure SF . Moreover, SF can be extracted and stored in lyophilized form for long-term storage and, later on, can be dissolved in organic solvents such as HFIP (1,1,1,3,3,3-hexafluoro-2-propanol) and formic acid to produce SF scaffolds in different forms including fibers, gels, or sponges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations